(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Periprosthetic femoral fractures around hip stems are complications following hip arthroplasty. They require stable fixation for early mobilization and optimal recovery. Locked plating with cables is an emerging technique that enhances stability in such fractures. Objective: To evaluate the treatment outcomes of locked plating with cables in periprosthetic femoral fractures. Methods: A retrospective study was conducted on 40 patients who underwent locked plating with cables for periprosthetic femoral fractures at Cho Ray Hospital from April 2020 to April 2024. Clinical and radiographic outcomes, including bone healing rates and functional hip scores, were assessed. Results: The mean age of patients was 65.9 ± 19.8 years, with a male-to-female ratio of 1:1.2. The most common cause of fracture was living accident (80%). The average operative time was 142 minutes. Blood transfusion was required in 32 out of 40 cases (80%) due to significant intraoperative blood loss. At the 6-month follow-up, the bone healing rate was 95%, with a mean Harris Hip Score of 78.8. Complications included 2 cases of superficial infection (5%) and 2 cases of decubitus ulcer (5%). Conclusion: Locked plating with cables provides stable fixation, allowing early mobilization and achieving high rates of bone healing. This technique is an effective option for treating periprosthetic femoral fractures.